Anti oxidant Property of Plumbagin on Fibrosarcoma Induced Rats - Keerthidaa G2, Vidyalakhsmi K3, Bhavani G4, Rukmani Devi S5, P. Jayamathi1*, (Recent Research in Science and Technology, 2010)
Enhanced generation of reactive oxygen/ nitrogen species (ROS/RNS) and the ensuing phenomenon in the form of oxidative stress have been implicated in the etiology of cancer. Anti oxidants due to their ability to neutralize the toxic free radicals or damage induced by them have potential applications in the prevention and/or therapy of human ailments. Plumbagin, a napthaquinone derivative from Plumbago zeylanica and has been claimed to possess antitumor effect. Elevated levels of lipid peroxides and decreased activities of antioxidant enzymes such as catalase, superoxide dismutase and Glutathione peroxidase were assayed in plasma, liver and kidney of fibrosarcoma induced rats, and the levels significantly reverted back to normal, after treatment with plumbagin. These observations clearly suggested the antitumor potency of plumbagin in experimentally induced fibrosarcoma in rats.